Mineral Deposits, Exploration and Ore-Reserve Estimation - Jones, Odwyn; Aspandiar, Mehrooz; Dugdale, Allison; Leggo, Neal; Glacken, Ian; Smith, Bryan (The business of mining, 2020)
This third volume of the Business of Mining set commences with "Our Earth, its Minerals and Ore Bodies", followed by a review of mineral exploration and sampling of mineral deposits. It continues with detailed sections covering the reporting of mineral resources and reserves in Australia, and concludes with the basic principles and application of the various methods of estimating the in-situ mineral resources and ore reserves. The books were written primarily for undergraduate applied geologists, mining engineers and extractive metallurgists and those pursuing course-based postgraduate programs in mineral economics